Visualization of submicron Si-rods by SPR-enhanced total internal reflection microscopy - Rengevych, O.V.; Beketov, G.V.; Ushenin, Yu.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The potential of surface plasmon resonance-enhanced total internal reflection microscopy for visualization of submicron particles has been demonstrated using submicron-sized silicon rods as a test object. Submicron Si-rods were deposited onto the surface of a plasmon-supporting gold film by sedimentation from suspension, and their images were obtained using optical microscope with SPR excitation. Quality of images obtained in this way was compared with images viewed from the prism side in the SPR microscopy configuration. Specific features of light scattering from filiform objects are discussed. The study was aimed at development of a novel type of SPR-based biosensor relied upon direct count of biological species of interest (bacteria, viruses, large biomolecular complexes).